2015
DOI: 10.1002/ece3.1839
|View full text |Cite
|
Sign up to set email alerts
|

Postdispersal nepotism in male long‐tailed macaques (Macaca fascicularis)

Abstract: Cooperative behaviors are promoted by kin selection if the costs to the actor are smaller than the fitness benefits to the recipient, weighted by the coefficient of relatedness. In primates, cooperation occurs primarily among female dyads. Due to male dispersal before sexual maturity in many primate species, however, it is unknown whether there are sufficient opportunities for selective tolerance and occasional coalitionary support for kin selection to favor male nepotistic support. We studied the effect of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Coalitions were another mechanism yearlings used to maintain dominance rank, and we found evidence for nepotism, or kin bias, as coalitions were more frequent among peers that were reared together (and therefore either maternally or paternally related). Similarly, a recent study also found support for post-dispersal nepotism in male long-tailed macaques (Macaca fascicularis), as males that entered into a troop with relatives resided in that troop and maintained a higher rank for longer (Gerber, Krützen, de Ruiter, van Schaik, & van Noordwijk, 2016), suggesting that kin support continues in new social groups, similar to our results. Our results also suggest that coalitions were primarily a mechanism to reinforce, rather than challenge, the hierarchy (Smith et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Coalitions were another mechanism yearlings used to maintain dominance rank, and we found evidence for nepotism, or kin bias, as coalitions were more frequent among peers that were reared together (and therefore either maternally or paternally related). Similarly, a recent study also found support for post-dispersal nepotism in male long-tailed macaques (Macaca fascicularis), as males that entered into a troop with relatives resided in that troop and maintained a higher rank for longer (Gerber, Krützen, de Ruiter, van Schaik, & van Noordwijk, 2016), suggesting that kin support continues in new social groups, similar to our results. Our results also suggest that coalitions were primarily a mechanism to reinforce, rather than challenge, the hierarchy (Smith et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Assuming the case where parallel immigrations occurred was not by chance, some advantages must be conferred for one or both males. Since in crested macaques, males of the same age are likely to be half-brothers due to the high reproductive skew in a group, post dispersal nepotism is likely to increase a male’s direct and indirect reproductive benefit as recently found in long tailed macaques 43 . However, since only a few males immigrated at the same day, and only one pair could be confirmed to show parallel dispersal (and therefore could be potential half-brothers), it is unlikely to be a strategy widely adopted by males.…”
Section: Discussionmentioning
confidence: 87%
“…Many of these studies have focused on species closely related to Assamese macaques, so it is plausible that the males in our study are capable of recognizing unfamiliar kin through similar mechanisms. Moreover, males can disperse from their natal group together with kin they grew up with and should be able to discriminate those joint dispersal partners as kin (Albers & Widdig, 2012; Gerber, Krützen, de Ruiter, van Schaik, & van Noordwijk, 2016; Perry, 2012; Schoof, Jack, & Isbell, 2009). Yet, based on a still limited sample size, even plausibly familiar kin do not seem to be preferred bonding partners in male Assamese macaques (average Elo‐rating over groups and years of related males known to have left the natal group together = 0.495, N = 11, based on five unique dyads).…”
Section: Discussionmentioning
confidence: 99%